Wind tunnel and numerical study of a straight-bladed vertical axis wind turbine in three-dimensional analysis (Part I: For predicting aerodynamic loads and performance). (1st July 2016) - Li, Qing'an; Maeda, Takao; Kamada, Yasunari; Murata, Junsuke; Kawabata, Toshiaki; Shimizu, Kento; Ogasawara, Tatsuhiko; Nakai, Alisa; Kasuya, Takuji
Abstract: This paper presents a straight-bladed VAWT (vertical axis wind turbine) model for the evaluation of aerodynamic forces and inertial contributions to rotor blade deformation. In this paper, a two-bladed VAWT is proposed and analyzed with CFD (computational fluid dynamics) and wind tunnel experiments in three-dimensional (3D) investigation. In wind tunnel experiments, pressure measurement system is presented to measure the pressure acting on a single blade of straight-bladed VAWT in the spanwise direction. In numerical analysis, 3D CFD models have been performed to simulate the aerodynamic forces characteristics of VAWT with k–ε SST (Shear Stress Transport) ( k–ε ) turbulence model. From comparing the results of the wind tunnel experiments and numerical analysis, it is found that the fluid force decreased with the increase of spanwise positions excluding the position of support structure. Furthermore, according to the result from six-component balance, the waveforms of the power coefficient C pw have similar characteristics and show smaller values than CFD calculations. Highlights: Pressure is measured in the spanwise direction by multiport pressure measurement devices. Aerodynamic forces are simulated with k –ε Shear Stress Transport turbulence model. Pressure coefficient is large at the blade center height and small at the blade tip. Fluid force shows small value at the position of support structure.